Clinical utility of targeted next-generation sequencing assay in IDH-wildtype glioblastoma for therapy decision-making. Issue 7 (8th December 2021) - Lim-Fat, Mary Jane; Youssef, Gilbert C; Touat, Mehdi; Iorgulescu, J Bryan; Whorral, Sydney; Allen, Marie; Rahman, Rifaquat; Chukwueke, Ugonma; McFaline-Figueroa, J Ricardo; Nayak, Lakshmi; Lee, Eudocia Q; Batchelor, Tracy T; et al.
Abstract: Background: Targeted gene NGS testing is available through many academic institutions and commercial entities and is increasingly incorporated in practice guidelines for glioblastoma (GBM). This single-center retrospective study aimed to evaluate the clinical utility of incorporating NGS results in the management of GBM patients at a clinical trials-focused academic center. Methods: We identified 1011 consecutive adult patients with pathologically confirmed GBM ( IDH wt or IDH mut) who had somatic tumor sequencing (Oncopanel, 500 cancer gene panel) at DFCI from 2013–2019. Clinical records of all IDH wt GBM patients were reviewed to capture clinical trial enrollment and off-label targeted therapy use based on NGS results. Results: Of the 557 IDH wt GBM patients with sequencing, 182 entered clinical trials at diagnosis (32.7%) and 213 (38.2%) entered after recurrence. Sequencing results for 130 patients (23.3%) were utilized for clinical trial enrollment for either targeted therapy indications (6.9 % upfront and 27.7% at recurrent clinical trials and 3.1% for off-label targeted therapy) or exploratory studies (55.4% upfront and 6.9% recurrent clinical trials). Median overall survival was 20.1 months with no survival difference seen between patients enrolled in clinical trials compared to those who were not, in a posthoc analysis. Conclusions: While NGS testing has become essential for improved molecular diagnostics, our study illustrates that targeted gene panels remain underutilized for selecting therapy in GBM- IDH wt. Targeted therapy and clinical trial design remain to be improved to help leverage the potential of NGS in clinical care.